A Review of the Impact of Post-2010 International & Regional Political Developments on the Downturn of Turkey's Economy - Seyfeddin Neslinebi; Santi Rahmawati (Inclusive Society and Sustainability Studies, 2024)
In the post-2010 era, Turkey faced a volatile geopolitical landscape marked by the Arab Spring, the Syrian Civil War, shifting alliances, and heightened tensions with Western countries. These political challenges have had significant economic repercussions, including declining foreign direct investment, deteriorating currency stability, and decreased investor confidence. Additionally, domestic political shifts have exacerbated Turkey's financial vulnerabilities, such as consolidating power under President Recep Tayyip Erdogan and increasing centralization of economic decision-making. This study examines the effects of regional and international developments (European Union, the United States, Russia) since 2010 on the decline of the Turkish economy. Literature review approach were used to gather relevant academic papers, reports, and other secondary data. The thematic analysis was taken to make this research more comprehensive and cover the pivotal aspects. The findings highlight the need for policy reforms to navigate international political tensions and financial recovery. The research underscores the intertwined nature of politics and economics in Turkey, demonstrating how political instability has deepened the economic downturn. Moreover, Turkey is geopolitically within active social structures and has powerful political, social, and economic relations with Western and Eastern societies. Therefore, any event that develops in the East or the West can quickly and effectively affect Turkey's political, social, and economic structure.